ОЛНОО ӨРГӨГДСӨН МОНГОЛ УЛСЫН ЭДИЙН ЗАСГИЙН ТУСГААР ТОГТНОЛЫН АСУУДАЛД - Г. Цэнджав (Politology, 2023)
When in the 29th of December of 1911 the Mongols established own state for strengthening it and liberation own territory from the Manchu-Chinese troops unite the rest of Mongolia under the Mongol rule need a huge amount of financial sources. So make the fund rising in the Mongolian ground was impossible. For that purpose the Mongols seek the financial aid from Russia and heavily talk how the Mongols should have own financial sources and how payback the Russian loan and how the Mongols should develop their financial ability. All those internal policy moods in the Mongolian society described in this article using the historical sources of that time.